Faunal Change in Eastern Africa at the Oldowan – Acheulean Transition - (:unkn) unknown (My University, 2018)
The Early Pleistocene transition from the Oldowan to the Acheulean in eastern Africa was roughly contemporaneous with a number of other events commonly assumed to be connected with hominin evolution. I review here the large mammal evidence, well-documented in several major eastern African sites. Definite conclusions are hard to reach because of temporal gaps in the fossil record, and very patchy history of many lineages, but I conclude that, although some groups do show some turnover during this period, most of them did not change more than before or after it. We may conclude that this cultural change did not seriously impact the faunal assemblage. In addition, we may surmise that, since climate change at this period, if any, did not seriously impact the fauna, it is unlikely to have played a major role in human evolution at that time.
Keywords: African Research